The Nature of Support Provided to Gifted Primary School Students Is Based on the Teacher's Concept of Giftedness - Tomasz Knopik; Urszula Oszwa (Ignatianum University Press, 2022)
The aim of the research was to identify the type of support that teachers provide to gifted students in grades 4-6 of primary schools in Poland in relation to their concepts of giftedness. Teachers' understanding of the category of gifted students was analyzed: What do they find crucial in identifying gifted students? What areas of gifted students' development are most important to them? Are there differences in the strategies for supporting gifted students between teachers who have different concepts of giftedness and who teach different subjects? The research was conducted on a group of 188 teachers using the standardized 20-item Balanced Development of Gifted Students Questionnaire. It helped identify the scope of the teachers' activities in the cognitive, emotional/social, motivational, and creative spheres. It was shown that the dominant concept of giftedness among the surveyed teachers was cognitive and that their activities supporting gifted students were mainly aimed at mental development and knowledge acquisition. Support of the emotional/social sphere of gifted students was least frequently indicated by the respondents. There was consistency between the type of support provided and the teacher's preferred concept of giftedness. There were significant differences in the definition of giftedness and the related type of support between teachers of different subjects. The subject which they taught also significantly differentiated the number of students identified as gifted: The most gifted students were identified by the art teachers, while the least were identified by the math teachers. The results may serve as guidelines for developing teachers' competencies in working with gifted students by popularizing the concept of balanced development and making them aware of the links between beliefs about giftedness and the type of support provided.